Czasy napoleońskie widziane oczyma podmiejskiego plebana. Notatki księdza Bonawentury Najgrakowskiego w księdze chrztów parafii św. Michała w Gnieźnie - Śrama, Marcin (Studia Europaea Gnesnensia, 2024)
In 1791-1811, Rev. Bonawentura Najgrakowski would record events which were important for the town and the Polish nation in the margins of the Baptismal Register of the St Michael parish in Gniezno. In his brief notes, he placed particular emphasis on political developments which, in his opinion, were to culminate in independence of the Republic. Much of his attention focused the figure of the first French consul and later Emperor Napoleon Bonaparte. To date, Rev. Najgrakowski’s notes have not become the subject of scholarly inquiry.